Prevention of musculoskeletal injuries in recreational field hockey: the systematic development of an intervention and its feasibility - Vincent Gouttebarge; Victor Zuidema (BMJ Open Sport & Exercise Medicine)
Objective This article describes the systematic development of an intervention for the prevention of lower extremity injuries in field hockey and the assessment of its feasibility.Methods The intervention was developed according to the first four steps of the intervention mapping and knowledge transfer scheme processes, mostly based on focus group interviews with experts in field hockey and injury prevention (needs assessment; objective and target groups; content selection; development). Subsequently, a quasi-experimental research (one-group post-test design) was conducted among 35 young field hockey players and 7 coaches. Participants were asked to use the intervention for 3 weeks, and the degrees of relevancy, suitability, satisfaction and usability of the intervention were assessed by means of a questionnaire and a group interview.Results First, the needs assessment conducted among the main actors within recreational field hockey revealed that an injury prevention intervention was needed, ideally delivered through videos via an application for smartphone/tablet or website. Second, the objective and target groups of the intervention were defined, namely to prevent or reduce the occurrence of lower extremity injuries among both young and adult recreational field hockey players. Third, warming-up exercises were selected as preventive measures and strategies (eg, core stability, strength, coordination). Last, the ‘Warming-Up Hockey’ intervention was developed, consisting of a warm-up programme (delivered by coaches including more than 50 unique exercises). The relevancy, satisfaction and usability of ‘Warming-Up Hockey’ were positively evaluated, but two main alterations were made: the duration of the ‘Warming-up Hockey’ was reduced from 16 to 12  min and a match-specific warm-up was added.Conclusion The feasibility of ‘Warming-Up Hockey’ was positively assessed by players and coaches. Prior to its nationwide implementation, the effectiveness of the intervention on injury reduction among field hockey players should be conducted.